Knowledge, Attitudes and Behaviours Concerning Sustainable Development among Grade 9th Students in the Northern Province of Sri Lanka - Nithlavarnan, A.; Sinnathambi, K.; Gunawardana, G.I.C. (National Centre for Advanced Studies in Humanities and Social Sciences, 2016)
Contemporary Sri Lanka face (a number) of sustainability issues. Providing an appropriate education to the educational community and the general public is one of the more effective strategies to help solve these problems. Education for Sustainable development (ESD)-enriches education forms, the foundation for these initiatives. Compared with other countries, Sri Lanka is far behind in focusing on the ESD initiatives and is facing a challenge with the task of embedding ESD at national, school, and subject levels. This study attempts to investigate how students at junior secondary level demonstrate their understanding, attitudes and behaviours concerning different aspect of sustainable development and to examine as to how these impacts on the important for future development of ESD in Sri Lanka general Education. The study follows a survey research method. 397 Grade-9 students in Secondary schools from the 12 educational zones in the Northern Province of Sri Lanka are taken as the survey sample. Schools have been selected by using the stratified random sampling method. The Questionnaire was adopted based on Michalos et al. (2011) The results reveal that students perceived fair to strong understanding on the different aspect of Sustainable Development (SD) (mean = 1.97). The result indicate that students have positive attitudes (mean = 1.99) and favorable behaviour (mean = 1.79) concerning different aspects of SD. Moreover, there are significant gender differences in the knowledge as a feature of SD (t = 2.678; p < 0.05). However, no significant gender differences in the behavior (t = 1.467; p > 0.05) and attitudes (t = 1.197; p > 0.05). There are significant differences in School Type (F= 5.630; p > 0.05) and education zone (F = 3.2987; p > 0.05) on knowledge as a feature of SD whilst, there are no significant differences in school type and education zone on behaviour and attitudes.
Keywords: Knowledge; Attitudes; Behaviours; Stainable Development; Grade 9 th Students